Factors that improve and maintain public servants motivation: a study of Jabatan Ketua Menteri Melaka (JKMM) / Hamdan Abu Kassim - Abu Kassim, Hamdan (Faculty of Business and Management, 2014)
This study conducted to identify the factors that improve and maintain public servants motivation. The researchers have chosen Jabatan Ketua Menteri Melaka (JKMM) to represent this study. Researchers have listed three variables which are reward and recognition, training and development, and work environment as the independent variables and motivation as the dependent variable. The researchers distributed 70 set of questionnaires to respondents which are Jabatan Ketua Menteri Melaka (JKMM). This study discussed the factors that improve and maintain motivation at Jabatan Ketua Menteri Melaka (JKMM) and those factors will be the outcome of this study. The finding and analysis were made based on Statistical Package for Social Science (SPSS) version 20.0 to analyze the data. The finding of this study proves that the reward and recognition, training and development, and work environment can positively to improve and maintain motivation. Training and development appear to be the most influenced factor towards employee motivation in Jabatan Ketua Menteri Melaka (JKMM).